Catalytic upgrading of biomass-derived raw gas in fluidized bed gasifiers - Ruivo, Luís Carlos Marques (2023)
Gasification of lignocellulosic biomass is a thermochemical conversion route with high potential to reduce the dependence on fossil fuels. Still, current gasification technologies present technical limitations that turn their large-scale exploitation unfeasible, mostly due to the presence of tar in the producer gas that incites several operational constrains. Amongst the existing techniques for tar removal, catalytic hot gas cleaning has been proposed as an attractive approach, highlighting the need to explore alternative catalysts with potential applicability in gasification processes with limited economic feasibility. The present thesis aimed to explore the catalytic potential of low-cost iron-based materials to improve the quality of biomass-derived gas. In order to obtain insights about the dependence of catalyst performance on the thermochemical conditions of the gasification process, a graphical approach based on experimental data and thermodynamic modelling were developed. Attention was given to potential deactivation mechanisms resulting from gas-solid interactions, as well as to the stability of relevant iron catalytic systems when exposed to biomass gas atmospheres. Thermodynamic predictions suggest that minimal changes in the redox atmosphere of the gasifier can have a significant impact on the catalytic nature of iron. Moreover, controlled operating parameters contributes to enhance the tolerance of iron-based catalysts to deactivation by coke, H₂S poisoning and/or carbonation. One should also consider suitable composition changes to enhance their redox properties and their thermochemical stability, possibly combined with microstructural or nanostructural development during materials processing. A novel Fe₂₋ₓNixTiO₅ catalyst with low Ni load was developed and tested for downstream upgrading of biomass-derived gas. The material was prepared by combining mechanical activation and microwave firing. The catalytic performance towards steam reforming reactions was studied in a fixed bed tubular reactor, using a mixture of C₇H₈ and C₁₀H₈ as model tar compounds, as well as downstream a fluidized bed gasifier. The reforming studies revealed a high conversion of model tar compounds for reaction temperatures above 700 ºC. The addition of Ni promoted both steam reforming and water-gas-shift reactions, increasing H2 content in the producer gas. The Fe₂₋ₓNixTiO₅ catalyst also exhibited 78 % decrease in total tar concentration at 800 ºC when applied in a fixed bed reactor, located downstream of a bench-scale fluidized bed gasifier. A gradual decline in the catalytic activity was observed with increased time on stream, possibly because of structural changes in iron active sites and sulphur chemisorption on Ni surface. The in-situ performance of a highly gas permeable Fe₂₋ₓMnxO₃ catalyst during biomass gasification was also studied, seeking to promote tar conversion by oxidation reactions. The catalysts were obtained through the functionalization of porous ceramic structures by incipient wetness impregnation, with subsequent microwave-assisted thermal treatment. Particular attention was given to the influence of the operating conditions on the tar conversion ability. The Fe₂₋ₓMnxO₃ catalyst showed high activity in converting tar compounds with increasing reaction temperature and equivalence ratio, while decreasing the residence time showed a negative impact on catalyst performance. Catalytic conversion of tar compounds followed a redox-type mechanism, facilitated by the variable oxygen stoichiometry of mixed Fe/Mn oxides. Further analysis of the spent catalysts revealed sulphur interactions, which increased with temperature and did not correlate with the catalytic performance. This can be explained by the wide redox stability range of divalent manganese oxide and its enhanced tolerance to H2S. Under optimal operating conditions, the catalyst promoted 83 % decrease in tar concentration, as well as a relevant increase in gasification parameters, such as the gas yield (0.81 to 0.93 Nmdry,gasᵌ∙kgdry,fuel⁻¹), carbon conversion efficiency (53.1 to 65.1 %) and cold gas efficiency (50.7 to 61.6 %). One also sought to explore the in-situ operation of composite catalysts based on siderite and concrete precursor mixtures for H₂-enriched gas production. A cost-effective granulation method has been developed for the preparation of catalysts, followed by thermal treatment in N₂ atmosphere. Catalytic performance towards water-gas-shift reaction was studied in a fixed bed reactor and Taguchi experimental design was applied to clarify the influence of experimental parameters on H₂ promotion. The influence of the experimental parameters on H₂ promotion had the following order: reaction temperature (43.1 %), concrete mass ratio (30.2 %), and steam to carbon molar ratio (26.7 %). These contributions were associated with the redox behaviour of iron oxides with mixed valence, derived from the siderite precursor, with corresponding O₂ storage ability, and extended conditions for carbonation/decarbonation of the concrete precursor, which may provide CO₂ storage ability. When integrated into the freeboard zone of a bubbling fluidized bed gasifier, one observed a significant increase in the H₂:CO molar ratio (1.9 to 3.3), H2 yield (33.8 to 48.6 gH₂∙kgdry,fuel⁻¹), carbon conversion efficiency (54.1 to 58.6 %) and cold gas efficiency (55.0 to 60.9 %). Though the catalyst exhibited resistance to sintering, post-mortem analysis suggests loss of active species after repeated cycles of regeneration due to thermal-induced stresses, which caused a slight decrease in activity. In conclusion, the results of this thesis demonstrate that the application of iron-based catalysts in biomass gasification is feasible when dealing with low-cost precursors, showing similar performance to other catalysts found in literature. However, additional improvements should be considered before those materials might be applicable in future gasification concepts.